O projeto de educação especial na educação superior: pedagogias em disputa - Ferraz, Ana Paula dos Santos (2022)
This study is linked to the Education Post-Graduation Program at the Federal University of Santa Maria, in the Research Line Special Education, Inclusion and Difference, and to the theoretical studies of the Psychology of Education and Inclusive Education Study and Research Group – GEPEIN. Understanding Special Education as a part of Education and considering the contradictions of social phenomena (MARX, ENGELS, 2009), the objective is to analyze which pedagogical actions and practices permeate the special education project in higher education, considering Law nº 13.409/2016, which makes it obligatory for federal universities to reserve places for people with disabilities. In light if this, the qualitative investigation was organized in the following stages: survey of the knowledge production in the field; mapping of the public higher education institutions in the country; elaborating and sending online forms in order to know the reality of the institutions and delimitate inclusion and exclusion criteria for participating in the research; analysis of the answers and elaborating an interview script; contact via e-mail with the institutions that answered the form and invitation to participate in an interview via Google Meet; scheduling and performing the interviews. Out of the 63 mapped higher education institutions, 21 answered the forms. Out of these, 17 interviews were performed, which were recorded with the participants’ consent and then transcribed. The content analysis followed three stages: pre-analysis, which consisted in listing the official documents that guide education in the perspective of inclusive education, formulating the tensions and objectives of the investigation, as well as establishing the categories of analysis; exploration of the material, characterized by reading and taking excerpts from the answers and transcribing the interviews, grouping them according to the categories of analysis and, lastly, the treatment of the results, in which we tried to reflect and theorize from the theoretical frameworks of THC. The research results point to a dismantlement in higher education, evidenced by: budget reduction, extinction/lack of vacancy code for specific professionals of the special education field, overworked teachers and technicians, privatization of services, among others. In this sense, the practices linked to the field of special education are performed, in their majority, by scholarship students in training, who do not have a functional tie to the institution and do not have labor rights and by outsourced professionals, such as psychopedagogues. It was observed that the reasoning behind the actions and practices are permeated by a technical/new school pedagogy where there is an acknowledgment of the individual differences and a greater worry with methods, techniques and instruments as a way to objectify the pedagogical work (SAVIANI, 2001; GARCIA, 2017; VAZ, 2017). Thus, we defend that there is a need, in higher education, of a special education project grounded on the fundamentals of historic-critical pedagogy (SAVIANI, 2010), present in the development of the Articulated Teaching in which the special education teacher acts collaboratively with the other teachers in mediating the scientific knowledge aiming for the omnilateral formation of the students supported by special education.